Targeting Neuroinflammation in Neovascular Retinal Diseases - Wang, Tianxi; Tsirukis, Demetrios I.; Sun, Ye (Frontiers in Pharmacology, 2020)
Retinal blood vessels provide necessary energy, nutrients and oxygen in order to support visual function and remove harmful particles from blood, thus acting to protect neuronal cells. The homeostasis of the retinal vessels is important for the maintenance of retinal visual function. Neovascularization is the most common cause of blindness in many ocular diseases including retinopathy of prematurity, age-related macular degeneration and diabetic retinopathy. Previous studies have shown that inflammatory mediators are known key regulators in retinopathies, but their causal link has been elusive. Although inflammation is often thought to arise from inflammatory cells like macrophages, neutrophils, and resident microglia, retinal neurons have also been reported to contribute to inflammation, through inflammatory signals which mediate blood vessel growth. Therefore, it is important to explore the detailed mechanisms of how neuroinflammation effects retinal neovascularization. This review summarized current research on the relationship between retinal angiogenesis and neuroinflammation in retinopathies as well as the potential effects of neuroinflammation on retinal neovascularization in different animal models.